IDENTIFICATION OF BACTERIA FROM POST TIN MINING POND AND THEIR ABILITY TO FORM BIOFILMS AT DIFFERENT PH - Ciatri Herafi; Rahmad Lingga; Andri Kurniawan (Universitas Medan Area, 2022)
A number of water quality indicators in the tin post-mined pond of a certain age indicate that the water condition is acidic, low dissolved oxygen content, low cation exchange capacity, and polluted by heavy metals. Restoration of the water quality of post-tin mining pond can use microorganisms as bioremediation agents. Microorganisms live by forming microbial community structures called biofilms. The aims of this study was to identify and find out the optimal pH of biofilm formation biofilm-forming bacteria from post-tin mining pond. The steps of research method was the isolation of bacteria by the spread plate technique, the biofilm formation test by the crystal violet technique, and the identification of bacteria macroscopically, microscopically, and physiologically. The isolation results showed that the highest bacterial density was at station 3 with a total of 8.1x103 cfu/ml. The results of the visualization of biofilm formation find out the A8 isolate at pH 5 with the most concentrated staining, while the highest Optical Density (OD) value for each pH was 0.11245 (pH 3) for A8 bacteria, 0.1901 (pH 5) for I1 bacteria and 0.1901 (pH 5) for A8 bacteria of 0.08945 (pH 7). There were 14 isolated bacterial belonging to the Genus Branhamella, Bacteroides, Aeromonas, Bacillus and Clostridium 08945 (pH 7). Based on identification results, biofilm-forming bacterial isolates from the tin-mining pond of Rebo Village there were 14 isolated bacterial belonging to the Genus Branhamella, Bacteroides, Aeromonas, Bacillus and Clostridium 08945 (pH 7). There were 14 isolated bacterial belonging to the Genus Branhamella, Bacteroides, Aeromonas, Bacillus and Clostridium.